2020
DOI: 10.1111/mec.15648
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of convergent adaptation to Alpine environments in three Brassicaceae species

Abstract: It has long been discussed to what extent related species develop similar genetic mechanisms to adapt to similar environments. Most studies documenting such convergence have either used different lineages within species or surveyed only a limited portion of the genome. Here, we investigated whether similar or different sets of orthologous genes were involved in genetic adaptation of natural populations of three related plant species to similar environmental gradients in the Alps. We used whole‐genome pooled po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 101 publications
5
33
0
Order By: Relevance
“…We also did not find any evidence that our gene reuse candidates were under weaker selective constraint than other genic loci genome-wide. Nevertheless, we cannot exclude that changes in constraint contribute to the decreasing probability of gene reuse across Brassicaceae, as was also reported in (61). Second, protein evolution studies reported patterns of diminishing amino acid convergence over time due to the decreasing probability of hemiplasy, i.e., the gene tree discordance caused by incomplete lineage sorting and introgression (32, 33, 62).…”
Section: Discussionmentioning
confidence: 78%
“…We also did not find any evidence that our gene reuse candidates were under weaker selective constraint than other genic loci genome-wide. Nevertheless, we cannot exclude that changes in constraint contribute to the decreasing probability of gene reuse across Brassicaceae, as was also reported in (61). Second, protein evolution studies reported patterns of diminishing amino acid convergence over time due to the decreasing probability of hemiplasy, i.e., the gene tree discordance caused by incomplete lineage sorting and introgression (32, 33, 62).…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, we cannot exclude that changes in constraint contribute to the decreasing probability of gene reuse across Brassicaceae, as was also reported in ref. 61. Second, protein evolution studies reported patterns of diminishing amino acid convergence over time due to the decreasing probability of hemiplasy (i.e., the gene tree discordance caused by incomplete lineage sorting and introgression) (33,34,62).…”
Section: Discussionmentioning
confidence: 99%
“…Resequencing of 35 individuals from across the species range (Laenen et al, 2018) and 304 from the western Swiss Alps (Rogivue et al, 2019) represent outstanding examples for sequencing of natural plant populations, and the publicly available data offer opportunities for future population genomic analyses. Additional genomic resources for A. alpina include the whole-chloroplast genome sequence (Melodelima & Lobréaux, 2013) and a more fragmented reference genome assembly using individual and pooled-sample sequencing of a Swiss population (Rellstab et al, 2020).…”
Section: Systematic and Taxonomic Considerations Of Genus Arabismentioning
confidence: 99%